2019
DOI: 10.1371/journal.pone.0225070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the higher-order structure of the Profile of Emotional Competence (PEC): Confirmatory factor analysis and Bayesian structural equation modeling

Abstract: Emotional competence (EC) reflects individual differences in the identification, comprehension, expression, regulation, and utilization of one’s own and others’ emotions. EC can be operationalized using the Profile of Emotional Competence (PEC). This scale measures each of the five core emotional competences (identification, comprehension, expression, regulation, and utilization), separately for one’s own and others’ emotions. However, the higher-order structure of the PEC has not yet been systematically exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…A novel aspect of our study is the assessment of the trait dimensions of interpersonal EC through the PEC. Our results support the utility of assessing both intra‐ and interpersonal EC dimensions in unveiling the specific associations between abilities and dispositional tendencies (Nozaki et al, 2019). Importantly, when assessed separately from intrapersonal EC, interpersonal EC seems to have a greater impact on emotion recognition than the diagnosis of AN.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A novel aspect of our study is the assessment of the trait dimensions of interpersonal EC through the PEC. Our results support the utility of assessing both intra‐ and interpersonal EC dimensions in unveiling the specific associations between abilities and dispositional tendencies (Nozaki et al, 2019). Importantly, when assessed separately from intrapersonal EC, interpersonal EC seems to have a greater impact on emotion recognition than the diagnosis of AN.…”
Section: Discussionsupporting
confidence: 87%
“…PEC is still a fairly new instrument, however, several studies have confirmed its sound psychometric properties (Batselé et al, 2019;Kotsou et al, 2018;Nozaki, 2015Nozaki, , 2018. A recent study investigated PEC higher-order structure in a large international sample, finding support for the separation of intra-and inter-personal EC components (Nozaki et al, 2019). For this study, translated items were created through back-translation.…”
Section: Emotional Competencementioning
confidence: 99%
“…To sum up, the PEC and the TEIQue show convergent validity in many aspects, but also displayed some unique features that make them conceptually different from each other. As evidenced by our findings, and in line with theoretical considerations underlying the PEC and the TEIQue (Brasseur et al, 2013;Nozaki et al, 2019;Petrides, 2009), the main distinction is that the PEC differentiates explicitly and systematically competences related to intrapersonal and interpersonal emotions, while the TEIQue aggregates both, with some TEIQue subscales spanning both aspects, while other TEIQue subscales target specifically only one aspect. This characteristic can be considered a limitation of the TEIQue, given being able to differentiate clearly between intrapersonal and interpersonal emotional process appears critical both conceptually and at the applied level when designing interventions.…”
Section: Convergent Validity Between the Teique And The Pecsupporting
confidence: 83%
“…The PEC (Brasseur et al, 2013) measures how individuals deal with intrapersonal and interpersonal information, on the five core EC, namely identification, expression, understanding, regulation, and use of emotions. The main difference with the TEIQue is that the PEC splits explicitly each of the five main EC into two dimensions, intrapersonal and interpersonal, while the TEIQue integrates both intrapersonal and interpersonal information in its factors (Brasseur et al, 2013;Nozaki et al, 2019;Petrides, 2009). This distinction allows to better understand the relationship of EC with outcomes (Pekaar et al, 2020), given certain aspects may be more related to intrapersonal EC, such as health (Mikolajczak et al, 2015;Nozaki & Koyasu, 2016), perceived stress (You et al, 2020), or executive functions (Vaughan et al, 2020), while other may be more connected to interpersonal EC, such as relationships (Brasseur et al, 2013).…”
mentioning
confidence: 99%
“…These studies all suggest intrapersonal and interpersonal EC may play different roles in the moderation of CV. In addition, a recent study analyzed data from diverse samples and revealed that the modified target based structure distinguishing between intrapersonal EC and interpersonal EC with residual correlations among competence types fitted better than alternative models, emphasizing the importance of distinguishing between the two domains (Nozaki, Puente-Martínez, & Mikolajczak, 2019). However, to our knowledge, previous studies have only focused on the moderating effect of abilities to handle ones' own emotion.…”
Section: Emotional Competence As a Potential Moderatormentioning
confidence: 99%